Peranan Gracilaria verrucosa dalam Menurunkan Nitrogen (N) dan Mangan (Mn) Melalui Sistem Polikultur dan Monokultur - Ahmad Fuad Masduqi; Munifatul Izzati (Media Farmasi Indonesia, 2014)
ABSTRACT Gracilaria verrucosa is one type of seaweed that has the potential to be exploited and developed mainly used in ponds. The aims of this research is to study the role of Gracilaria verrucosa in reducing the content of Nitrogen (N) and Mangan (Mn) in the sediment on the pond. This research is conducted in the village pond Mororejo, Kendal and in the Biology laboratory, department of Biology faculty of Sains and Mathematics Diponegoro University. This research was designed by random complete design. The research was the methods of shrimp monoculture, monoculture Gracilaria verrucosa and polyculture containing shrimp, milkfish and Gracilaria verrucosa. The resulted data was analized by Analysis of Variance (ANOVA) continued by real difference test Duncan Multiple Range Test (DMRT) in 95% significance level. The parameters in this research were N and Mn content in the sediment. The results showed that the content of N and Mn in sediments more on shrimp monoculture farming systems than in monoculture Gracilaria verrucosa and polyculture of Gracilaria verrucosa.